A cell transportation solution that preserves live circulating tumor cells in patient blood samples. Issue 1 (December 2016) - Stefansson, Steingrimur; Adams, Daniel; Ershler, William; Le, Huyen; Ho, David
Abstract Background Circulating tumor cells (CTCs) are typically collected into CellSave fixative tubes, which kills the cells, but preserves their morphology. Currently, the clinical utility of CTCs is mostly limited to their enumeration. More detailed investigation of CTC biology can be performed on live cells, but obtaining live CTCs is technically challenging, requiring blood collection into biocompatible solutions and rapid isolation which limits transportation options. To overcome the instability of CTCs, we formulated a sugar based cell transportation solution (SBTS) that stabilizes cell viability at ambient temperature. In this study we examined the long term viability of human cancer cell lines, primary cells and CTCs in human blood samples in the SBTS for transportation purposes. Methods Four cell lines, 5 primary human cells and purified human PBMCs were tested to determine the viability of cells stored in the transportation solution at ambient temperature for up to 7 days. We then demonstrated viability of MCF-7 cells spiked into normal blood with SBTS and stored for up to 7 days. A pilot study was then run on blood samples from 3 patients with metastatic malignancies stored with or without SBTS for 6 days. CTCs were then purified by Ficoll separation/microfilter isolation and identified using CTC markers. Cell viability was assessed using trypan blue or CellTracker™ live cell stain. Results Our results suggest that primary/immortalized cell lines stored in SBTS remain 90 % viable for > 72 h. Further, MCF-7 cells spiked into whole blood remain viable when stored with SBTS for up to 7 days. Finally, live CTCs were isolated from cancer patient blood samples kept in SBTS at ambient temperature for 6 days. No CTCs were isolated from blood samples stored without SBTS. Conclusions In this proof of principle pilot study we show that viability of cell lines is preserved for days using SBTS. Further, this solution can be used to store patient derived blood samples for eventual isolation of viable CTCs after days of storage. Therefore, we suggest an effective and economical transportation of cancer patient blood samples containing live CTCs can be achieved.